COMPARATIVE ANALYSIS OF HEALTH LEVELS AT BANK NEO COMMERCE & BANK JAGO - Novia Nur Aliftiani; Muhammad Firdaus; Nely Supeni (MBA : Journal of Management and Business Aplication, 2024)
Bank is a business entity that collects funds from the public in the form of savings and distributes them to the public in the form of credit and/or other forms in order to improve the standard of living of the people at large. Based on Indonesia Bank Regulation Number 13/1/PBI/2011, the soundness level of a bank is analyzed using the Risk Profile, Good Corporate Governance, Earnings, Capital (RGEC) method. This study aims to determine the soundness of Neo Commerce Bank and Jago Bank and their comparisons in 2019 – 2021 using the RGEC method. This research is comparative research. The data taken is secondary in the form of the annual financial reports of Neo Commerce Bank and Jago Bank for 2019 – 2021. The assessment in this study uses the Non Performing Loan (NPL) ratio, Loan to Deposit Ratio (LDR), Self Assessment, Return On Assets (ROA), Net Interest Margin (NIM), and Capital Adequacy Ratio (CAR). The results showed that the soundness level of banks using the RGEC method at Neo Commerce Bank and Jago Bank in 2019-2021 both received Composite Rating 2 (PK-2) and entered the Healthy category.